Pemeriksaan Kadar Yodium Pada Ikan Asin Olahan Nelayan Kota Bengkulu - Nita Anggreani Nita; Tri Nur Hayati (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The fishing community in Bengkulu City processes salted fish products of various types and sizes of salted sea fish using krosok salt. With a fairly high salty taste, the iodine content in salted fish should meet the standards set by the government. This study was conducted to examine the iodine content of fish processed by fishermen in Bengkulu City whether it is in accordance with SNI. This research is descriptive with a purposive sampling technique using 6 types of salted fish samples. A gradual examination of the qualitative analysis to see the change in the color of the sample to dark purple if it is positive for iodine. Meanwhile, quantitative determination of iodine content was carried out by iodometric titration. The results of the analysis showed that all negative samples contained iodine and salted fish products were not in accordance with SNI 3556-2016.